Resensitisation of Methicillin-Resistant Staphylococcus aureus to Conventional Antibiotics in the Presence of an Engineered Enzybiotic - Salim Manoharadas; Basel F. Al-Rayes; Mohammed Abdulaziz M. Almuzaini; Yasser Muteq Almohammadi (MDPI AG, 2023)
Methicillin-resistant Staphylococcus aureus (MRSA) is one of the most dreadful pathogens relevant in community and nosocomial-related infections around the world. Resensitising MRSA to antibiotics, once it became resistant, was a tough choice due to the high adaptability of this bacteria to savage conditions. This study aimed to create a chimeric enzybiotic against MRSA and test its efficiency, either individually or in combination with antibiotics. The novel enzybiotic BAC100 was constructed by fusing the catalytic domain from the bacteriocin BacL1 from Enterococcus faecalis with the cell-wall-binding domain from protein P17 of Staphylococcus aureus bacteriophage ϕ44AHJD. Apart from its partial lone activity, BAC100 was found to resensitise the MRSA strain to traditional antibiotics, including ampicillin and tetracycline. Both drugs were able to reduce live MRSA cells by 85 and 90%, respectively, within 60 min of treatment together with BAC100. However, no significant activity was observed against MRSA when these drugs were tested independently, pointing to the inherent resistance of MRSA against these conventional antibiotics. To our knowledge, this is one of the first instances where an engineered enzybiotic was found to resensitise MRSA to conventional antibiotics. This study will pave the way for the development of similar peptides that can be used together with antibiotics against gruesome pathogens of clinical importance.